DANGER FOR PUBLIC TRANQUILITY: EXPULSION OF FOREIGNERS AND LABOR CONFLICT IN COSTA RICA, 1894-1936. - Llaguno, José Julián (2019)
The article aims to characterize the process of historical construction of the pernicious foreigner in the period from 1894 to 1936 in order to show how the mechanism of expulsion was used as a political tool that sought to control and purge immigration in the country. Above all, the text defends that this mechanism worked against a specific segment of the population, the working class, and its implementation shows the intention to contain the worker’s associativism as well as the development of socialist ideas considered contrary to the national morality. To support this approach, the researcher worked with primary sources from the National Archive of Costa Rica and Historic National Archive of Spain, selecting those administrative files opened for the crime of disturbance of public tranquility and complementing the analysis with the current legislation on the subject and the literature on labor disputes. The study focuses on the cities of San José and Limón, which are the cities where the cases that were found are concentrated.